Small freshwater ecosystems with dissimilar microbial communities exhibit similar temporal patterns. Issue 9 (25th March 2021) - David, Gwendoline M.; López‐García, Purificación; Moreira, David; Alric, Benjamin; Deschamps, Philippe; Bertolino, Paola; Restoux, Gwendal; Rochelle‐Newall, Emma; Thébault, Elisa; Simon, Marianne; Jardillier, Ludwig
Abstract: Despite small freshwater ecosystems being biodiversity reservoirs and contributing significantly to greenhouse fluxes, their microbial communities remain largely understudied. Yet, microorganisms intervene in biogeochemical cycling and impact water quality. Because of their small size, these ecosystems are in principle more sensitive to disturbances, seasonal variation and pluri‐annual climate change. However, how microbial community composition varies over space and time, and whether archaeal, bacterial and microbial eukaryote communities behave similarly remain unanswered. Here, we aim to unravel the composition and intra/interannual temporal dynamic patterns for archaea, bacteria and microbial eukaryotes in a set of small freshwater ecosystems. We monitored archaeal and bacterial community composition during 24 consecutive months in four ponds and one brook from northwestern France by 16S rRNA gene amplicon sequencing (microbial eukaryotes were previously investigated for the same systems). Unexpectedly for oxic environments, bacterial Candidate Phyla Radiation (CPR) were highly diverse and locally abundant. Our results suggest that microbial community structure is mainly driven by environmental conditions acting over space (ecosystems) and time (seasons). A low proportion of operational taxonomic units (OTUs) (<1%) was shared by the five ecosystems despite their geographical proximity (2–9 km away), making microbial communities almost unique in each ecosystem and highlighting the strong selective influence of local environmental conditions. Marked and similar seasonality patterns were observed for archaea, bacteria and microbial eukaryotes in all ecosystems despite strong turnovers of rare OTUs. Over the 2‐year survey, microbial community composition varied despite relatively stable environmental parameters. This suggests that biotic associations play an important role in interannual community assembly.